Simplify this expression 4p+9+(-7p)+2=?

I like to rearrange the equation to get like terms next to eachother. Everything attached to the variable p goes together, and everything that’s just an integer goes together.

4p+9+(-7p)+2 – Equation
4p+(-7p)+9+2 – Rearrange
-3p+9+2 – Combine p terms
-3p+11 – Combine constants

I think your question is wrong.

Anyhow solution is
4p + (-7p) +9+2 just rearrange
= -3p+11 that is all.

4p+9+(-7p)+2=?
4p+9-7p+2=?
4p-7p+9+2-?=0
-3p+11-?=0
3p+?=11

since all you have is adding just add the common variables. So in this case you want to add 4p and (-79) together and you should get -3p. Then you add 9 and 2 and you get 11. So your answer will be -3p+11=?

-3p+11

Leave a Comment